Silver Nanoparticle Synthesis Using an Inkjet Mixing System - Maki, Taisuke; Takeda, Saki; Muranaka, Yosuke; Mae, Kazuhiro (Frontiers in Chemical Engineering, 2021)
Individual nanoscale silver particles were produced using an inkjet mixing system. First, the behaviors of colliding droplets were investigated to prepare to conduct the synthesis without splitting merged droplets. When small droplets collided, they merged to form droplets that stayed in a state of coalescence at a higher discharging velocity. In addition, by changing the orientation at the collision point, the droplet velocity could be increased. Then, silver nanoparticle synthesis was conducted under conditions that avoided droplet splitting. Smaller particles were produced by higher-velocity collisions for all the examined droplet sizes. When droplets were 50 – 100 µm, an average particle diameter of 2.5 nm was produced. In addition, when droplets of different sizes collided, they formed a continuous supply of precursor, which subsequently resulted in production of particles with uniform size.